PENGUATAN KEMAMPUAN MANAJEMEN KEUANGAN SEBAGAI DASAR PENGEMBANGAN HOBI PRODUKTIF SISWA MENUJU EKONOMI KREATIF - Lotmariani Bakkara; Adinda Nurul Racmawati; Siti Aisah Ainurrohmah; Mudzakir (Abdi Jurnal Publikasi, 2026)
The development of the creative economy requires young generations to have good financial management skills to support productive activities based on hobbies. However, many students have creative potential but still lack understanding of basic financial management. This Community Service Program (PKM) aims to improve students’ knowledge and skills in managing personal finances and developing productive hobbies into economic opportunities. The methods used include observation, financial literacy education, simple financial recording training, business capital simulation, and discussion of productive hobby ideas. The results show an increase in students' understanding of financial management, ability to record income and expenses, and awareness of hobby-based business opportunities. This program is expected to support the development of student independence and contribute to strengthening the creative economy sector.